Characterization of the commercially-available fluorescent chloroquine-BODIPY conjugate, LynxTag-CQGREEN, as a marker for chloroquine resistance and uptake in a 96-well plate assay - Loh, C; Suwanarusk, R; Lee, Y; Chan, K; Choy, K; Rénia, L; Russell, B; Lear, M; Nosten, F; Tan, K; Chow, L (Public Library of Science, 2014)
Chloroquine was a cheap, extremely effective drug against Plasmodium falciparum until resistance arose. One approach to reversing resistance is the inhibition of chloroquine efflux from its site of action, the parasite digestive vacuole. Chloroquine accumulation studies have traditionally relied on radiolabelled chloroquine, which poses several challenges. There is a need for development of a safe and biologically relevant substitute. We report here a commercially-available green fluorescent chloroquine-BODIPY conjugate, LynxTag-CQGREEN, as a proxy for chloroquine accumulation. This compound localized to the digestive vacuole of the parasite as observed under confocal microscopy, and inhibited growth of chloroquine-sensitive strain 3D7 more extensively than in the resistant strains 7G8 and K1. Microplate reader measurements indicated suppression of LynxTag-CQGREEN efflux after pretreatment of parasites with known reversal agents. Microsomes carrying either sensitive- or resistant-type PfCRT were assayed for uptake; resistant-type PfCRT exhibited increased accumulation of LynxTag-CQGREEN, which was suppressed by pretreatment with known chemosensitizers. Eight laboratory strains and twelve clinical isolates were sequenced for PfCRT and Pgh1 haplotypes previously reported to contribute to drug resistance, and pfmdr1 copy number and chloroquine IC50s were determined. These data were compared with LynxTag-CQGREEN uptake/fluorescence by multiple linear regression to identify genetic correlates of uptake. Uptake of the compound correlated with the logIC50 of chloroquine and, more weakly, a mutation in Pgh1, F1226Y.